A STUDY OF STUDENTS’ PLANNING OF METACOGNITIVE STRATEGIES IN LISTENING COMPREHENSION - ELFI ELFI (Ta'dib, 2014)
The students have a problem in comprehending the text in listening comprehension. It was prompted by the idea that metacognitive stratetegies is the crucial important to solve the problem in listening comprehension. By using these strategies, it helped students to plan, monitor, solve, and evaluate their learning to foster their listening comprehension. One of strategy in metacognitive is planning strategies.  This article is intendedto find out what planning  of metacognitive strategies used by students and  the way they apply it in listening comprehension.Based on the research has conducted by the researcher, The students had applied metacognitive strategies but some of them did not do it in the correct ways in listening comprehension.  It can be concluded that the result of the study indicated that the planning of metacognitive strategies used by the students in listening comprehension need to be develop and increase in to the correct ways to get better comprehension in listening.Key words:    metacognitive strategies, planning strategies, listening comprehension.